Evolving thresholds for liver transplantation in hepatocellular carcinoma: A Western experience - Michelle R. Ju; Adam C. Yopp (Annals of Gastroenterological Surgery, 2020)
Abstract Hepatocellular carcinoma (HCC) is the second leading cause of cancer‐related deaths worldwide. Once considered an experimental treatment with dismal survival rates, liver transplantation for HCC entered a new era with the establishment of the Milan criteria over 20 years ago. In the modern post‐Milan‐criteria era, 5‐year survival outcomes are now upwards of 70% in select patients. Liver transplantation (LT) is now considered the optimal treatment for patients with moderate to severe cirrhosis and HCC, and the rates of transplantation in the United States are continuing to rise. Several expanded selection criteria have been proposed for determining which patients with HCC should be candidates for undergoing LT with similar overall and recurrence‐free survival rates to patients within the Milan criteria. There is also a growing experience with downstaging of patients who fall outside conventional LT criteria at the time of HCC diagnosis with the goal of tumor shrinkage via locoregional therapies to become a candidate for transplantation. The aim of this review article is to characterize the various patient selection criteria for LT, discuss balancing organ stewardship with outcome measures in HCC patients, present evidence on the role of downstaging for large tumors, and explore future directions of LT for HCC.